Synthetic, structural, and spectroscopic studies of mixed sandwich Ru(II) complexes involving η6-p-cymene with monodentate fluorine-containing phosphines or phosphites. Issue 1 (2nd January 2016) - Lee, John P.; Hankins, Michael J.; Riner, Ashley D.; Albu, Titus V.
Abstract: Syntheses, structures, spectroscopy, and calculated structures for several Ru(II) complexes involving p -cymene and either fluorine-containing phosphines or phosphites are reported. The complexes are readily prepared by ligand substitution reactions from [{Ru( p -cymene)Cl2 }2 ] to produce [Ru( p -cymene)(L)Cl2 ] {L = P(C6 H4 - p -F)3 (1 ), P(C6 H4 - p -CF3 )3 (2 ), P(C6 H3 ( m -CF3 )2 )3 (3 ), PPh3 (4 ), P(OCH2 CF3 )3 (5 ), P(OCH(CF3 )2 )3 (6 ), and POMe3 (7 )}. The structures for all seven complexes are supported by UV–vis and multi-nuclear NMR spectroscopy. Five complexes are characterized by single-crystal X - ray crystallography (1, 3, 5 –7 ) and exhibit a distorted octahedral structure involving three donors from one phosphine or phosphite ligand, two chlorides, and the facially coordinating η 6 - p -cymene ligand. Electronic structure theory computations have been performed on1 –7 along with the theoretical [Ru( p -cymene){P(C6 F5 )3 }Cl2 ] (8 ). For all complexes, the HOMO is primarily Ru ( d xy or ) in character. The LUMO shifts from primarily Ru ( d xz or d yz ) to primarily phosphine ligand π * as the number of fluorines increases. Abstract :